The Modelization of Built Heritage. Comparing BIM Processes for Architectural Types (diségno, 2019)
The study of an historical architecture and the heterogeneous set of information linked to has important repercussions in many areas: from documentation, to the planning of interventions, to the management of cultural heritage. The goal of total data integration is now pursued by the BIM processes; their application for the historical buildings involves methodological and technical implications both in the survey field and in the representation, linking the modeling operations to the massive data acquisition. These activities are very complex because of the use of libraries of standardized elements, in conflict with the uniqueness and complexity of the historical form. Two different case studies for eras and construction techniques are analyzed. For both the standardization process of the building process is evident, such as the presence of serial elements with easily recognizable geometries, handcrafted in the first case, industrially in the second. The parametric approach to the modeling describes, through creation of nidified elements with hierarchical structure, the logical process of decomposing the form.
Keywords: HBIM; architectural typo; standard; modeling; database